2003
DOI: 10.1111/j.1349-7006.2003.tb01352.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum carotenoids and mortality from lung cancer: a case‐control study nested in the Japan Collaborative Cohort (JACC) Study

Abstract: To investigate whether high serum levels of carotenoids, tocopherols, and folic acid decrease risk of lung cancer in Japanese, we conducted a case-control study nested in the Japan Collaborative Cohort (JACC) Study. A total of 39 140 subjects provided serum samples at baseline between 1988 and 1990. We identified 147 cases (113 males and 34 females) of death from lung cancer during an 8-year follow-up. Of the subjects who survived to the end of this follow-up, 311 controls (237 males and 74 females) were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 38 publications
2
29
1
Order By: Relevance
“…44 We found that serum folic acid levels were not clearly inversely associated with lung cancer death in men or women, as same as previous study. 8 However, further investigation is needed to clarify this issue; the sample size for serum folic acid in the present study was limited.…”
Section: Subject Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 We found that serum folic acid levels were not clearly inversely associated with lung cancer death in men or women, as same as previous study. 8 However, further investigation is needed to clarify this issue; the sample size for serum folic acid in the present study was limited.…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…7 We previously found that high serum levels of -carotene (AC) and BC can reduce the risk of lung cancer death, in a case-control study nested in a large-scale Japanese cohort. 8 Serum levels of AC and BC are affected by daily lifestyle elements such as diet, smoking and alcohol consumption, 9,10 and this appears to be partly responsible for sex differences in lung cancer risk. Recent intervention studies of BC administration have shown no inverse association between BC administration and lung cancer incidence among non-Asians.…”
mentioning
confidence: 99%
“…Numerous epidemiological studies are available reporting a positive association between decreased risk of chronic diseases such as cancer and cardiovascular disease and lycopene intake through dietary intake of tomatoes and tomato products (Rissanen et al, 2003;Agarwal and Rao, 2000;Bramley, 2000;Giovannucci, 1999;Erhardt et al, 2003;Ito et al, 2003;Sesso et al, 2003). No adverse effects related to tomato and tomato product intakes were reported.…”
Section: Human Data On Lycopenementioning
confidence: 99%
“…[4][5][6] During the Japan Collaborative Cohort Study (JACC Study) for Evaluation of Cancer Risk sponsored by the Ministry of Education, Science, Sports and Culture of Japan (Monbusho), a food frequency questionnaire was used to assess dietary habits of the subjects at baseline survey. In addition, blood samples were collected from all subjects at baseline, 7 and serum concentrations of carotenoids were measured to evaluate cancer risk at lung, 8 colon and rectum, 9 and urothelial system (pelvis, ureter, and bladder). 10 To validate these results, we have compared serum carotenoid concentrations with dietary habits in a sample set of the JACC Study.…”
mentioning
confidence: 99%
“…A second possibility is that sub-This study was primarily designed to validate the food frequency questionnaire and serum concentrations of carotenoids in the nested case-control studies as parts of the JACC Study. [8][9][10] Controls of those nested case-control studies were thought to represent the general population of the JACC study, and adequate to the sample set of this study. However, discussion applied in a different situation may be limited; e.g., most subjects of the JACC Study lived in rural areas, where dietary habits may be different from those in urban areas; subjects who donated blood samples were around 30% of whole respondents to the baseline questionnaire survey, therefore, they may be more health-conscious.…”
mentioning
confidence: 99%